Identification of Rawan Accidental Areas In Suranaya - Gresik Toll Road - Bayu Kusumo Nugroho; Melly Setya Haryanti (Jurnal Teknologi Transportasi dan Logistik, 2020)
Traffic accident is the transportation problem that needs to be addressed immediately. During the year 2015 – 2016 recorded as many as 258 accidents happened on highways in Surabaya-Gresik. The purpose of this research is to identify areas prone to accidents on highways Surabaya – Gresik and handling efforts to reduce accidents. This study uses secondary data, namely data obtained from a crash in pt. Margabumi Matraraya and the data analysis using the method of EAN (Equivalent Accident Number) and analyzed to obtain the accident-prone areas with using the method of BKA (Control Over) and the UCL (Upper Control Limit). The results of the analysis show that there are 5 point accident-prone location i.e. KM 07 08, KM, KM 12, KM 15, and 16 KM. Efforts to reduce the accidents mitigation on accident-prone location is performing actions such as technical barriers, installation location warning accident-prone, marka profile, warning lamp, , rumble strip, VMS, and road study.